2020
DOI: 10.1101/2020.05.25.114553
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The impact of genetic diversity on gene essentiality within theE. colispecies

Abstract: Bacteria from the same species can differ widely in their gene content. In E. coli, the set of genes shared by all strains, known as the core genome, represents about half the number of genes present in any strain. While recent advances in bacterial genomics have enabled to unravel genes required for fitness in various experimental conditions at the genome scale, most studies have focused on model strains. As a result, the impact of this genetic diversity on core processes of the bacterial cell largely remains… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 74 publications
1
9
0
Order By: Relevance
“…2A). These results were confirmed in a recent and separate assessment of gene essentiality among a diverse group of E. coli, demonstrating the absence of emrE, yddA, mdtM, and acrF from the core genome (in this instance the core was defined as genes present in 90% of strains examined) (63). Our phylogenetic analysis highlights that these poorly conserved proteins either are isolated from other family members (e.g., EmrE and YddA) or phylogenetically cluster with homologous proteins (e.g., either MdtM and MdfA or AcrF and MdtF) (11,60,64).…”
Section: Evolutionary Origins and Conservation Of Bacterial Drug Efflux Pumpssupporting
confidence: 66%
“…2A). These results were confirmed in a recent and separate assessment of gene essentiality among a diverse group of E. coli, demonstrating the absence of emrE, yddA, mdtM, and acrF from the core genome (in this instance the core was defined as genes present in 90% of strains examined) (63). Our phylogenetic analysis highlights that these poorly conserved proteins either are isolated from other family members (e.g., EmrE and YddA) or phylogenetically cluster with homologous proteins (e.g., either MdtM and MdfA or AcrF and MdtF) (11,60,64).…”
Section: Evolutionary Origins and Conservation Of Bacterial Drug Efflux Pumpssupporting
confidence: 66%
“…We recently identified a retron in a P4-like satellite prophage that is responsible for the essentiality of the exodeoxyribonuclease I SbcB in the E. coli strain H120 (36). Retrons are intriguing genetic elements that comprise a reverse-transcriptase (RT) and a multi-copy single-stranded DNA and were recently shown to form tripartite toxin/antitoxin (TA) systems involved in anti-phage defense (7,8,18,37).…”
Section: P4-like Satellite Phages Encode a Hotspot For Bacterial Immumentioning
confidence: 99%
“…Though there are known examples of how the fitness of one gene in a genome is influenced by the presence or absence of other genes, there has been no systematic, large-scale study of how genetic background, in terms of the presence or absence of genes in a genome, influences the fitness effect of an incoming gene (13). Recently, however, it has been shown that the genetic background of a genome has a direct effect on whether or not a gene is essential (39). We have little knowledge of why some lineages encode genes that others do not, and the extent to which the observed encoded genes influence the likelihood of successfully integrating other incoming genes.…”
Section: Discussionmentioning
confidence: 99%
“…We also propose, alongside the role that sharing function plays, that gene mobility could be an additional mechanism behind the formation of these gene-gene relationships. MGEs are a known link to gene essentiality and virulence in E. coli (4; 39; 43), and they have been implicated in driving accessory genome differences in a Listeria monocytogenes pangenome (44). Here, we have demonstrated that they also influence gene co-occurrences by uncovering hub genes and connected components linked to or encoded on MGEs (24; 25; 7; 45; 46; 47; 48; 49).…”
Section: Discussionmentioning
confidence: 99%